Evaluating the feasibility of the implementation of a multimedia web application called spacedeck for speaking practice purposes for students from levels 1 and 2 at the Language Center at the Catholic University of Santiago de Guayaquil. - Kim Kim, Carolina (2017)
The present project aimed to find difficulties associated with the development of the speaking skill at the Language Center at Catholic University and use Information Communication Technology for the enhancement and practice purposes for speaking and be able to offer it as a proposal. An evaluation research methodology was used to conduct this project as it was the most appropriate. To find out the difficulties associated with the development of speaking, 201 student surveys and 17 teacher surveys were collected and 5 teacher interviews were taken. The data was analyzed and quantified to reveal that lack of confidence, limited time, pressure to perform well, lack of understanding, use of mother tongue, and anxiety were amongst the highest voted difficulties within the development of speaking. Therefore, the multimedia web application called Spacedeck was used to develop a speaking practice tool and present it as a proposal for teachers to use to enhance speaking outside class hours. With the application, students can work from their home, collaborate, and do peer correction with other students to complete any speaking task assigned by the teacher using audio files, pictures, videos, and more. Teachers can have access to the spaces students have created anytime anywhere.